Synthesis and physical-chemical research of 7-((3-thio-4-r-4h-1,2,4-triazole-5-yl)methyl) theophylline carbonyl derivatives - Gotsulia, A. S.; Knyazevich, P. S.; Panasenko, O. I.; Knysh, Ye. G.; Гоцуля, А. С.; Князевич, П. С.; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Панасенко, А. И.; Кныш, Е. Г. (Запорізький державний медичний університет, 2015)
Aim. To analyze the carbonyl derivatives of 7-((3-thio-4-R-4H-1,2,4-triazole-5-yl)methyl)theophylline their mother substance was synthesized and its interaction with α-haloketones series was carried out. Methods and results. The physical-chemical properties of the obtained compounds have been studied and their structures have been confi rmed by elemental analysis, infrared spectrometry, 1H NMR spectrometry, UV spectrophotometry and gas chromatography mass spectrometry. Preliminary computer study of acute toxicity and biological activity has been also carried out. It has been determined that the obtained compounds may exhibit diuretic and analeptic activity and 1,2,4-triazole fragment can theoretically increase it. Conclusion. Preliminary prediction of acute toxicity has showed that the compounds are low-toxic. З метою дослідження карбонільних похідних 7-((3-тіо-4-R-4H-1,2,4-тріазол-5-іл)метил)теофіліну виконали синтез вихідної речовини та її взаємодію з рядом α-галогенкетонів. Досліджені фізико-хімічні властивості одержаних сполук і підтверджена їхня будова за допомогою елементного аналізу, ІЧ-спектрометрії, 1Н ЯМР-спектрометрії, УФ-спектрофотометрії та хромато-мас-спектрометрії. Здійснили попереднє комп’ютерне дослідження гострої токсичності та біологічної активності. Встановили, що отримані сполуки можуть проявляти діуретичну й аналептичну активності, а фрагмент 1,2,4-тріазолу теоретично може підсилювати цю активність. Попереднє прогнозування гострої токсичності показало: сполуки належать до малотоксичних. С целью исследования карбонильных производных 7-((3-тио-4-R-4H-1,2,4-триазол-5-ил)метил)теофиллина проведен синтез исходного вещества и его взаимодействие с рядом α-галогенкетонов. Исследованы физико-химические свойства полученных соединений и подтверждено их строение с помощью элементного анализа, ИК-спектрометрии, 1Н ЯМР-спектрометрии, УФ-спектрофотометрии и хромато-масс-спектрометрии. Проведённое предварительное компьютерное исследование острой токсичности и биологической активности. Установлено, что полученные соединения могут проявлять диуретические и аналептические активности, а фрагмент 1,2,4-триазола теоретически может усиливать эту активность. Предварительное прогнозирование острой токсичности показало, что соединения относятся к малотоксичным.
Синтез і фізико-хімічні дослідження карбонільних похідних 7-((3-тіо-4-R-4H-1,2,4-тріазол-5-іл)метил)теофіліну
Синтез и физико-химическое исследование карбонильных производных 7-((3-тио-4-R-4H-1,2,4-триазол-5-ил) метил)теофиллина
Keywords: 1,2,4-triazoles; Theophylline; Synthesis; IR Spectrometry; H NMR Spectrometry; 1,2,4-тріазол; Теофілін; Синтез; ІЧ-спектрометрія; Н ЯМР-спектрометрія; 1,2,4-триазол; Теофиллин; Синтез; ИК-спектрометрия; Н ЯМР-спектрометрия